PREGNANCY COURSE AND FETAL CONDITIONS IN WOMEN WITH EXTREMELY PREMATURE BIRTH - ANASTASIA V. Lebedeva; OLGA A. Zotova; VALENTINA I. Chernyaeva (Фундаментальная и клиническая медицина, 2017)
Aim. To study the course of pregnancy in women having an extremely premature labor. Materials and Methods. We recruited 100 women who delivered in Kemerovo Regional Perinatal Centre during 2014-2015 following stratification into two equal groups (n = 50): with extremely premature labor and with urgent delivery. Results. Women with extremely premature labor had a high prevalence of threatened miscarriage (56%), preterm premature rupture of membranes (42%), placenta previa (36%), polyhydramnios (22%), bacterial vaginosis (22%), and pre-eclampsia (8%). These patients were prescribed to glucocorticoids (72%), progestogens (28%), tocolytics (8%), and cervical pessary (8%). Newborns with extremely low birth weight (ELBW) had higher prevalence of asphyxia and required a respiratory support on average of 12 days. A majority (68%) of newborns with ELBW had congenital malformations, particularly congenital heart disease (34% of newborns with ELBW). Conclusion. Women with extremely premature labor are characterized by a high prevalence of pregnancy complications. Newborns with ELBW frequently have asphyxia, congenital malformations, and demand a longer respiratory support.